2010
DOI: 10.1158/0008-5472.can-10-0410
|View full text |Cite|
|
Sign up to set email alerts
|

Concurrent Suppression of Integrin α5, Radixin, and RhoA Phenocopies the Effects of miR-31 on Metastasis

Abstract: miR-31 inhibits breast cancer metastasis via the pleiotropic suppression of a cohort of prometastatic target genes that include integrin α 5 (ITGA5), radixin (RDX), and RhoA. We previously showed that the concomitant overexpression of ITGA5, RDX, and RhoA was capable of overriding the antimetastatic effects of ectopically expressed miR-31 in vivo. However, these prior studies failed to investigate whether the combined suppression of the endogenous mRNAs encoding these three proteins recapitulated the in vivo c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 15 publications
1
77
2
2
Order By: Relevance
“…Enforced expression of miR-409 could suppress the migration, invasion and metastasis of GC cells in vitro and in vivo. We further identified RDX, a putative pro-metastatic gene, 20,25 as a direct functional target of miR-409. To our knowledge, this is the first study to explore the role of miR-409 in cancer, and our results indicate that miR-409 acts to suppress metastasis in GC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Enforced expression of miR-409 could suppress the migration, invasion and metastasis of GC cells in vitro and in vivo. We further identified RDX, a putative pro-metastatic gene, 20,25 as a direct functional target of miR-409. To our knowledge, this is the first study to explore the role of miR-409 in cancer, and our results indicate that miR-409 acts to suppress metastasis in GC.…”
Section: Discussionmentioning
confidence: 99%
“…21 RDX was originally identified as a constituent of adherence junctions in the livers of rats, 36 and it has more recently been implicated in cancer progression and metastasis. 20,24,25,39 It has been reported that RDX may cooperate with ITGA5 and RhoA to affect three distinct steps in the invasionmetastasis cascade in vivo, local invasion, early post-intravasation events and metastatic colonisation. 25 Silencing of RDX has also been found to suppress the migration and invasion of GC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After potential target genes were uncovered via bioinformatic analysis, two tumor suppressor genes were found: LAST2 and PPP2R2A [58]. Further, when targeting ITGA5, RDX and RhoA, miR-31 may induce the recession of cancer cell metastasis and show suppressive tendencies [59].…”
Section: Some Mirnas That Show Both Oncogenic and Suppression Actionsmentioning
confidence: 99%